(untitled) (Research, Society and Development, 2020)
The use of antibiotics in clinical prescription has contributed greatly to the treatment of in-hospital patients, fighting bacterial infections. Despite this great contribution, another concern arises, which is the generation of bacterial resistance. This bacterial resistance to antibiotics is currently a public health issue, with worldwide prominence. The objective of the research was to verify in the Brazilian scientific literature, the risks of the use of antibiotics in the development of multi-resistant bacteria in the hospital environment. For this, a bibliographic search of a descriptive nature was carried out, carried out in the main databases such as Scielo, google scholar, pub med. The bibliographic survey showed that bacterial resistance currently represents a serious health problem and requires constant epidemiological surveillance. Socio-educational measures, in order to promote the rational use of these drugs, must be implemented, especially in the hospital environment, where this practice is even more worrying. It is necessary to highlight the important role of health professionals in the control of nosocomial infection, and the indiscriminate use of antibiotics in the development of multidrug-resistant strains.